Moldable superhydrophobic surfaces - Costa, A. M. S. (2016)
Moldable superhydrophobic surfacesÂ are produced by freely covering a solid surface with specifically designed microcapsules. Owing to the presence of Fe-particles within the former microcapsules, they can be temporarily fixed on different substrates using a permanent magnet. Such systems are prospective candidates for the fabrication of water/oil repellent surfaces, liquid marbles, or microfluidic channels and as templates for microspheres fabrication.